The Use of Natural Polymers to Enhance Oil Recovery - Fathaddin Muhammad Taufiq; Maulida Fajri; Hattu Valentyn Paul Bodywein; Ulfah Baiq Maulinda; Adianto Mohamad Obby; Afdi Rozi (E3S Web of Conferences, 2024)
This paper reports a laboratory study on the use of natural polymers to increase oil recovery. The use of natural polymers compared to synthetic polymers is more economical due to their abundant availability, renewability, biodegradability, and non-toxicity to the environment as they do not use chemicals. The purpose of this research is to measure the aqueous solution stability test and recovery factor produced by natural polymers through core flooding tests. The natural polymers used are Shrimp Chitosan, Crab Chitosan, Cyclea Barbata Miers, Mesona Palustris, and Seaweed. The methods used in this research are aqueous solution stability test and core flooding test. The shrimp chitosan solution used had a concentration from 5,000; 10,000 and 15,000 ppm and 2 salinities between 10,000 and 20,000 ppm. The crab chitosan solution used had a concentration from 5,000; 10,000 and 15,000 ppm with 2 salinities between 10,000 and 20,000 ppm. The Cyclea barbata Miers solution used had a concentration from 1,500; 2,500 and 3,500 ppm and 2 salinities between 7,000 and 15,000 ppm. The Mesona Palustris solution used had a concentration from 500; 1,000 and 2,000 ppm and 3 salinities from 10,000; 15,000 and 20,000 ppm. The Seaweed solution used had a concentration from 1,000; 2,000 and 3,000 ppm and 3 salinities from 5,000; 10,000 and 15,000 ppm. Sandpack is used as a porous media for crab chitosan experiments, while sandstone core is used for Cyclea Barbata Miers and Mesona Palustris with crude oil 44°API. The aqueous solution stability test showed that all polymer solution samples were clear for various concentrations and salinities. Except for the solutions of Cyclea barbata Miers and Masona palustris which are greenish and blackish respectively. Transmittance for shrimp and crab chitosan solutions shows a value of more than 80%. This shows that natural polymers are compatible with brine. Flooding tests were carried out to measure oil recovery related to the use of natural polymers. The experimental results showed that the best additional oil recovery was 10.3% using crab chitosan solution injection. The chitosan solution used had a concentration of 15,000 ppm and a viscosity of 1,729 cp. We can conclude that the addition of polymer can improve recovery factor.